2012
DOI: 10.1002/jmri.23696
|View full text |Cite
|
Sign up to set email alerts
|

Time‐resolved MR angiography of renal artery stenosis in a swine model at 3 Tesla using gadobutrol with digital subtraction angiography correlation

Abstract: Purpose: To establish the minimum dose required for detection of renal artery stenosis using high temporal resolution, contrast enhanced MR angiography (MRA) in a porcine model. Materials and Methods:Surgically created renal artery stenoses were imaged with 3 Tesla MR and digital subtraction angiography (DSA) in 12 swine in this IACUC approved protocol. Gadobutrol was injected intravenously at doses of 0.5, 1, 2, and 4 mL for time-resolved MRA (1.5 Â 1.5 mm 2 spatial resolution). Region of interest analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Due to the overall lengthy acquisition time of QISS‐MRA and the resulting time constraints, acquisitions were not repeated if poor image quality was detected in the present study. In contrast to CE‐MRA effects of poor bolus timing such as insufficient arterial contrast enhancement are not of concern; although, such effects are eliminated through use of dynamic CE‐MRA techniques . Although potential cost savings related to a lack of gadolinium chelate dose used for unenhanced MRA could be possible, this may be offset by longer scan acquisition times required and accompanying reductions in patient throughput.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the overall lengthy acquisition time of QISS‐MRA and the resulting time constraints, acquisitions were not repeated if poor image quality was detected in the present study. In contrast to CE‐MRA effects of poor bolus timing such as insufficient arterial contrast enhancement are not of concern; although, such effects are eliminated through use of dynamic CE‐MRA techniques . Although potential cost savings related to a lack of gadolinium chelate dose used for unenhanced MRA could be possible, this may be offset by longer scan acquisition times required and accompanying reductions in patient throughput.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences with high temporal resolution TWIST MRA from initial dose finding experiments using gadobutrol and gadoterate meglumine demonstrated that the total amount of Gd could be reduced to 1/5 of the typical (∼ 0.1 mmol/kg) dose for a CE‐MRA performed under clinical conditions. This dose‐finding study was performed using gadobutrol as the contrast media in a porcine model of renal artery stenosis (13). Transferring the observations of that preliminary study resulted in total injected volumes of 1 mL of gadobutrol and 2 mL of gadoterate meglumine for the high temporal resolution TWIST scan.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, assessment of Gdbased contrast agents with higher relaxivity as well as imaging at 3T could be warranted as possible ways to reduce the total amount of contrast agent injected, particularly in patients at risk for developing NSF. [17][18][19][20] In conclusion, consecutive acquisition of TCMRA and PWI using a supplementary injection of a Gdbased contrast agent can facilitate preoperative diŠerential diagnosis in patients with suspected brain metastasis. This method also increases the number and conspicuity of lesions detected in patients with suspected metastatic disease to the brain.…”
Section: Discussionmentioning
confidence: 99%